Articular cartilage: from formation to tissue engineering. (29th February 2016) - Camarero-Espinosa, Sandra; Rothen-Rutishauser, Barbara; Foster, E. Johan; Weder, Christoph
Abstract : A summary of the current state of cartilage tissue engineering underlying the relevant biological aspects that are important for scaffold design. Abstract : Hyaline cartilage is the nonlinear, inhomogeneous, anisotropic, poro-viscoelastic connective tissue that serves as friction-reducing and load-bearing cushion in synovial joints and is vital for mammalian skeletal movements. Due to its avascular nature, low cell density, low proliferative activity and the tendency of chondrocytes to de-differentiate, cartilage cannot regenerate after injury, wear and tear, or degeneration through common diseases such as osteoarthritis. Therefore severe damage usually requires surgical intervention. Current clinical strategies to generate new tissue include debridement, microfracture, autologous chondrocyte transplantation, and mosaicplasty. While articular cartilage was predicted to be one of the first tissues to be successfully engineered, it proved to be challenging to reproduce the complex architecture and biomechanical properties of the native tissue. Despite significant research efforts, only a limited number of studies have evolved up to the clinical trial stage. This review article summarizes the current state of cartilage tissue engineering in the context of relevant biological aspects, such as the formation and growth of hyaline cartilage, its composition, structure and biomechanical properties. Special attention is given to materials development, scaffold designs, fabrication methods, and template–cell interactions, which are of great importance to the structure and functionality of the engineered tissue.